Effects of dust deposition on solar reflectance of spacecraft radiators - Hiroki Gonome; Takamasa Hayashi; Takashi Unno; Sumitaka Tachikawa (Case Studies in Thermal Engineering)
This study investigates the effect of dust adhesion on the solar reflectance of spacecraft radiators—a critical factor in thermal control during planetary surface missions. While previous research has primarily addressed long-duration exposure to lunar or Martian dust, this work focuses on short-duration missions such as asteroid sample returns, where transient dust contact can impair radiator performance. A combination of experimental measurements and theoretical analysis was employed to evaluate the effects of dust particle composition, size, and adhesion amount on radiative properties. Using silver-coated glass substrates to simulate optical solar reflectors, spectral reflectance was measured before and after dust deposition under controlled laboratory conditions simulating electrostatic adhesion. The results indicated that TiO2 particles led to the greatest reduction in solar reflectance owing to their high absorptivity and strong electrostatic adhesion. Numerical simulations using Mie theory and radiative transfer models confirmed the experimental trends. Even moderate dust coverage caused up to 17 % reflectance loss, suggesting a substantial risk to thermal control. These findings highlight the need to account for material-dependent dust adhesion in a spacecraft radiator design. The results also support future countermeasures such as self-cleaning mechanisms for dust mitigation.